The Reflection of HOTS in EFL Teachers’ Summative Assessment - Pratiwi, N. P. Wismayani; Dewi, N. L. P. E. Sulistia; Paramartha, A. A. G. Yudha (Journal of Education Research and Evaluation, 2019)
This study is aimed at analyzing how summative assessments made by eleventh-grade English teachers reflect Higher Order Thinking Skills (HOTS). This was qualitative research that involved 3 English subject teachers in Senior High Schools in Bali, Indonesia. Meanwhile, the object of this research was summative assessment in the form of teacher-made test items for class XI Semester I in the academic year of 2018/2019. The items were analyzed by the document analysis method to determine the extent to which HOTS based on Revised Bloom's Taxonomy was reflected in the teacher-made test. Meanwhile, a one-on-one interview was conducted to obtain data on teacher knowledge about HOTS. The results of this study found that the percentage of HOTS-based teacher-made test items was 5.4% and was still limited to the cognitive level of Analyze (C4). From the results of the analysis, the cognitive levels of students measured were still in Lower Order Thinking Skills (LOTS). This was due to the fact that teachers did not fully understand the concept of Higher Order Thinking Skills. Furthermore, it was obtained from the interview that there was a discrepancy between the knowledge and performance of the teacher in the assessment. Therefore, teachers especially eleventh-grade English teachers have to learn more about HOTS and join training in developing HOTS-based items.